KINEMATIC ANALYSIS OF HORIZONTAL SEALER, VERTICAL SEALER, AND DRAWING ROLLER IN A TEMPEH PACKAGING MACHINE PROTOTYPE - Harsa Dhani; Redationo, Nereus Tugur; Natanael, Abel (Mechanical, Energy and Material (METAL), 2024)
The automatic packaging machine for tempeh improves both hygiene and efficiency in production. This Vertical Form Fill Seal model, equipped with a hole-punching mechanism, is examined in this study with a focus on the kinematics of its three key components: the horizontal sealer, vertical sealer, and drawing roller. The horizontal and vertical sealers are actuated by a single DC gear motor operating at 40 rpm, which manages their intermittent opening and closing. Additionally, a stepper motor running at 30 rpm controls the timing and drawing length of the plastic packaging, ensuring precise start and stop functions. The study's results revealed the following performance metrics for the machine's components: The horizontal sealer achieved a stroke distance of 62.4 mm, with the sealer operating at a maximum speed of 75.71 mm/s, and a total travel time of 1.65 seconds from closed to open position. For the vertical sealer, the stroke distance was 63 mm, with the sealer moving at maximum speed of 89.67 mm/s, and a travel time of 1.4 seconds from fully open to fully closed. The friction roller, driven by a stepper motor at 30 rpm, achieved a plastic withdrawal speed of 59.66 mm/s, allowing it to pull the plastic a maximum length of 167 mm within each 2.8-second cycle of the sealer components. It can be observed that continuous motor movement can be converted into intermittent back-and-forth motion using bar mechanisms, with the velocity at each position varying based on the length of the bars.